Induced sputum inflammatory mediator concentrations in chronic cough. - Birring, S; Parker, D; Brightling, C; Bradding, P; Wardlaw, A; Pavord, I (2004)
Previous studies have shown evidence of airway inflammation in patients with chronic cough and have suggested that the cough may be due to release of tussive mediators and activation of afferent sensory nerve endings. We measured the concentration of various proinflammatory and tussive mediators in induced sputum supernatants from 20 patients with cough variant asthma or eosinophilic bronchitis, 20 patients with nonasthmatic chronic cough, 22 patients with idiopathic chronic cough, and 18 healthy control subjects. We measured histamine, cysteinyl-leukotrienes, prostanoids (prostaglandin D2 and prostaglandin E2), and interleukin-8 by enzyme immunoassay. The median sputum histamine concentrations were significantly higher in patients with idiopathic chronic cough (8.0 ng/ml) and cough variant asthma/eosinophilic bronchitis (10.2 ng/ml) than in normal subjects (2.6 ng/ml; 95% confidence interval of difference from idiopathic chronic cough, 0.8 to 25.8 [p = 0.009] and 95% confidence interval of difference from cough variant asthma/eosinophilic bronchitis, 1.1 to 20.1 [p = 0.01]). Median sputum prostaglandin D2 and prostaglandin E2 concentrations were significantly higher in all categories of chronic cough. Our findings support the view that there is release of inflammatory and tussive mediators in patients with chronic cough and suggest that there might be similarities in the mechanism of cough in a diverse range of conditions.